منازعات الوظيفة العمومية - صالدي سعاد - بن شعبان ليلى (جامعة المسيلة, 2025)
Abstract: This study aims to shed light on the issue of civil service disputes and their resolution process, according to Order 06-03, which includes the General Basic Law for the Civil Service. These disputes are disputes or complaints raised by public sector employees regarding employment decisions or disciplinary procedures. Civil service disputes include arbitration before equal-member committees or administrative grievances before appeal committees. In some cases, they can develop into legal claims before administrative courts or the Council of State to resolve the dispute and provide protection for employees. The topic of civil service disputes is of great importance in the field of administrative law, given its impact on public employees and their relationship with the employing administration. The role of civil service disputes is evident in their representation of the rule of law. Therefore, a legal framework must be established to regulate this relationship, which is governed by the employee's career path. This framework includes a set of safeguards that employees can resort to whenever the administration violates the principle of legality in imposing penalties. These safeguards aim to provide the necessary protection for civil servants, whether administrative or judicial. These safeguards protect employees' rights from administrative abuse, such as the right to grievance, the right to resort to the judiciary, and the right to defense. Like other administrative disputes, civil service disputes can only achieve their goals and objectives through appeals filed by interested parties before administrative judicial bodies, in accordance with the rules and procedures specified in the Civil and Administrative Procedures Laws 08-09.
Keywords: Keywords: civil service disputes; administrative grievance; equal-member committees; administrative courts; Council of State